2022
DOI: 10.1101/2022.04.15.22273811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical EEG slowing induced by electroconvulsive therapy is better described by increased frontal aperiodic activity

Abstract: Electroconvulsive therapy (ECT) is one of the most efficacious interventions for treatment-resistant depression. Despite its efficacy, ECT's neural mechanism of action remains unknown. Although ECT has been associated with "slowing" in the electroencephalogram (EEG), how this change relates to clinical improvement is unresolved. Until now, increases in slow-frequency power have been assumed to indicate increases in slow oscillations, without considering the contribution of aperiodic activity, a process with a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…The observation that frontal aperiodic activity increases after a course of ECT supports our recent finding from a smaller, longitudinal study 25 . Furthermore, similar observations after a course of MST identify the increase in aperiodic activity as a potentially informative physiological change shared by both of these seizure-based treatments for depression.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The observation that frontal aperiodic activity increases after a course of ECT supports our recent finding from a smaller, longitudinal study 25 . Furthermore, similar observations after a course of MST identify the increase in aperiodic activity as a potentially informative physiological change shared by both of these seizure-based treatments for depression.…”
Section: Discussionsupporting
confidence: 90%
“…This conflation occurs even in the absence of oscillations, which are not omnipresent, but rather appear infrequently in short bursts [22][23][24] . So even if there are no oscillations, a large aperiodic signal can appear very similar to slowing in the EEG, as we have recently demonstrated 25 . This effect occurs because the EEG signal is a mix of oscillations and aperiodic activity, where oscillations are defined by concentrated power with a specific, narrow frequency band.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Literature provided mixed results about correlation between behavior and aperiodic activity. Some studies showed an association between the aperiodic parameters and cognition: Ostlund et al 35 found that a lower exponent during resting state predicted better performance on the dual-task "Stopping task", Smith and colleagues 89 showed that the aperiodic exponent was associated with cognitive performance and Ouyang et al 90 also evidenced that aperiodic activity during resting state was associated with cognitive processing speed. However, a study aiming to investigate aperiodic parameters and their link with cognition didn't show any correlation between aperiodic activity and behavior.…”
Section: No Correlation Between Behavior or Clinical Features And Ape...mentioning
confidence: 99%